Lying in Children’s Lives in Pinocchio Movie (2022) - Widianingsih; Elisabeth Ngestirosa Endang Woro Kasih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The study investigates the theme of lying habits depicted in the film Pinocchio (2022), focusing on the Social Pressure and the desire for acceptance, dynamic Influence, observation. This study used qualitative methodology to examine how Pinocchio's lies were portrayed, the consequences of his dishonesty, and the complex father-son relationship between Pinocchio and Geppetto. The film is analyzed as a reflection of social values, exposing the ethical dilemma of lying and its impact on human behavior. This analysis also explores the psychological motivations behind Pinocchio's lies and the role of parental influence in shaping honesty. The study concluded that the film provides insight into the importance of moral development and self-acceptance, as well as showing how social pressures and family relationships affect personal truth.